Histopathological profile of ovarian tumors at a tertiary care center of Nepal - Bhandari Thapa, Anuja; Shakya, Namo Buddha; Shrestha, Yashmin; Shrestha, Sujan; Banstola, Laxman (Journal of Pathology of Nepal, 2025)
Background: Ovarian tumors encompass a diverse group of neoplasms, including both benign and malignant forms with distinct clinical and histological features. In Nepal, ovarian cancer was the 10th most common cancer in 2022, with 643 new cases, representing 2.9% of all newly diagnosed cancers. Histopathological examination remains the definitive method for identifying and classifying ovarian tumors into benign, borderline, and malignant categories. This study aimed to determine the histopathological patterns of ovarian masses and examine their association with serum tumor markers. Materials and Methods: This is a cross-sectional descriptive study conducted over 2 years in the Department of Pathology at Paropakar Maternity and Women’s Hospital, Thapathali, Kathmandu, which included 319 patients who underwent ovarian biopsies. Histopathological examination was performed post-surgery and the descriptive evaluation of various histopathological subtype were conducted. Results: Among 319 cases of ovarian specimens, the majority of ovarian masses were benign, 292 cases (91.54%), malignant tumors, 21 cases (6.58%), and borderline tumors, 6 cases (1.88%). Mean age of patients presenting with benign tumors was 32 years, while it was 33 years for malignant tumors, and 51 years for borderline tumors. Conclusions: The majority of ovarian tumors are benign, with germ cell tumors, particulartly mature cystic teratomas being the most frequent histopathological subtype. Histopathological examination remains the definite gold standard for tumor classification.